2015
DOI: 10.1002/jms.3560
|View full text |Cite
|
Sign up to set email alerts
|

Separation of catechin epimers by complexation using ion mobility mass spectrometry

Abstract: Ion mobility coupled with mass spectrometry provides a fast and repeatable method to separate catechin epimers by previous complexation with selected chiral modifiers and transition metals. Several combinations with chiral ligands such as D- and L-amino acids and/or additional metal cations, chiral crown ethers, tartaric acid and heptakis(2,6-di-O-methyl)-β-cyclodextrin were screened for their ability to affect the separation efficiency. The clusters having the form of [2M + D-amino acid + Cu(2+) - 3H](-) (M s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In similar experiments with crown ethers, 12C4, 15C5, 18C6, and dibenzo‐30C10 were used by Clemmer in the ESI solution to shift the mobilities of peptide ions to different regions of the mobility spectrum, extending the ability to resolve components before mass spectrometry . Also, overlapping catechin epimers (M) were separated with D‐ and L‐amino acids (AA), chiral crown ethers, tartaric acid, cyclodextrins, and transition metals in the ESI solution by forming [2M + D‐AA + Cu 2+ ‐ 3H] − clusters …”
Section: Applications Of Mobility Shifts Upon Injection Of Buffer Gasmentioning
confidence: 69%
“…In similar experiments with crown ethers, 12C4, 15C5, 18C6, and dibenzo‐30C10 were used by Clemmer in the ESI solution to shift the mobilities of peptide ions to different regions of the mobility spectrum, extending the ability to resolve components before mass spectrometry . Also, overlapping catechin epimers (M) were separated with D‐ and L‐amino acids (AA), chiral crown ethers, tartaric acid, cyclodextrins, and transition metals in the ESI solution by forming [2M + D‐AA + Cu 2+ ‐ 3H] − clusters …”
Section: Applications Of Mobility Shifts Upon Injection Of Buffer Gasmentioning
confidence: 69%
“…Today, saponin characterization takes more and more advantage of the capabilities of mass spectrometry-based methods and LC-MS experiments are very efficient for saponin mixture characterization [6,9], often using accurate mass measurements (high-resolution MS-HRMS) and tandem mass spectrometry experiments (collision-induced dissociation-CID) [6,9,20]. We have reported the use of ion mobility spectrometry (IMS) [21,22] for saponin characterization [23,24]. We shown that isomeric saponins presenting different connectivities between the glycone and the aglycone moieties can be distinguished using IMS [24].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,9−13,15−18 As a result, it is not surprising that many recent publications on amygdalin analysis do not mention/identify the S-amygdalin, which is always present to some extent depending on the storage conditions, extraction solvents, and analytical procedures. Although in a few specific cases, using advanced instrumentation such as MS-MS that may allow differentiation of epimers, 19,20 ideally it is desired and usually necessary that the epimers are separated chromatographically. Thus, the separation of the natural and its unwanted isomerized amygdalin is best done chromatographically.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%